In situ ultrasonic monitoring of zeolite A crystallization from coal fly ash - Baser, Hasan-Hüseyin; Schwieger, Wilhelm; Hums, Eric; Musyoka, Nicholas M.; Petrik, Leslie F. (Catalysis Today, 2012)
In this study, high phase purity of zeolite A was prepared from coal fly ash precursors. The molar regime of both the clear solution extract and unseparated fly ash slurry was adjusted to achieve the right composition for zeolite A crystallization. The formation process for zeolite A from coal fly ash precursors was monitored in detail using an in situ ultrasonic system and was complemented by use of ex situ techniques such as XRD, FTIR, SEM and FTIR. The findings from both the in situ ultrasonic monitoring process and ex situ techniques clearly contributed significantly in unmasking the formation process of zeolite A from coal fly ash compared to previous studies reported in the literature. The study also enriches the existing body of literature by deeply investigating the gel-solution-crystal interactions starting from this complex feedstock. Comparable ultrasonic signals were generated when both clear and unseparated fly ash based precursor solutions were used during the zeolite synthesis process. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: In situ; Ultrasound; Coal fly ash; Zeolite A; Mechanism; Ageing process